ТАРБИЯ МЕТОДЛАРИ ЁРДАМИДА ЎҚУВЧИЛАР ОНГИГА СИНГДИРИШДА ОНА ТИЛИ ВА ЎҚИШ САВОДХОНЛИГИНИНГ ЎРНИ - Абдуллаев Холхужа (PEDAGOGS, 2024)
Abstract: The article focuses on the integration of Homeland prosperity in textbooks “Native language”, “Literature”, peace of the country, people’s well-being, social cooperation, harmony of the nation, sincere attitude to religion and others.